Characterization of A356/(fly ash + red mud) surface hybrid composite fabricated by friction stir processing. (2021) - Prasad, Rabindra; Kumar, Harikishor; Sinha, Nitesh K.; Tewari, S.P.; Singh, J.K.; Yadav, Siddharth; Deo, Manish
Abstract: Friction stir processing (FSP) is considered as a potential technique for fabrication of surface composites due to its solid-state nature along with its capability to modify microstructural features. In the present investigation, emphasis was on utilization of wastes (fly ash and red mud) as reinforcements instead of costly ceramics for surface composite fabrication in order to reduce overall cost along with environmental threats. Equal proportions of fly ash and red mud particles were reinforced on the surface of as cast A356 alloy to fabricate A356/(red mud + fly ash) hybrid surface composite via FSP. Microstructural features revealed evenly dispersed particles throughout the stir zone with an excellent bonding. Defects such as clustering, segregation along grain boundaries and pores at the interface were not observed. Compositional analysis indicated peaks related to matrix and reinforced particles only. Hardness and tensile strength in the stir zone improved significantly in comparison of as cast A356 alloy. This may be ascribed to grain refinement, uniform distribution of particles in the matrix and good interfacial strength between matrix and particulates.